2011
DOI: 10.1128/ec.00194-10
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of an Alternative Oxidase in Oxidative Stress and Mycelium-to-Yeast Differentiation in Paracoccidioides brasiliensis

Abstract: Paracoccidioides brasiliensis is a thermodimorphic human pathogenic fungus that causes paracoccidioidomycosis (PCM), which is the most prevalent systemic mycosis in Latin America. Differentiation from the mycelial to the yeast form (M-to-Y) is an essential step for the establishment of PCM. We evaluated the involvement of mitochondria and intracellular oxidative stress in M-to-Y differentiation. M-to-Y transition was delayed by the inhibition of mitochondrial complexes III and IV or alternative oxidase (AOX) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 78 publications
(89 reference statements)
1
54
0
Order By: Relevance
“…Whether this discrepancy is due to differences in strain backgrounds of C. albicans or the nature of the mitochondrial mutations remains to be determined. In the dimorphic pathogen P. brasiliensis, inhibition of mitochondrial respiration blocks the switch from filamentous to yeast morphology that is important for virulence (56). In conclusion, the available data from both direct and indirect studies support the notion that wild-type mitochondrial function is required for virulence.…”
Section: Mitochondria and Virulence Of Human Fungal Pathogenssupporting
confidence: 67%
See 1 more Smart Citation
“…Whether this discrepancy is due to differences in strain backgrounds of C. albicans or the nature of the mitochondrial mutations remains to be determined. In the dimorphic pathogen P. brasiliensis, inhibition of mitochondrial respiration blocks the switch from filamentous to yeast morphology that is important for virulence (56). In conclusion, the available data from both direct and indirect studies support the notion that wild-type mitochondrial function is required for virulence.…”
Section: Mitochondria and Virulence Of Human Fungal Pathogenssupporting
confidence: 67%
“…Indirect evidence for a role of mitochondria in the survival of fungal pathogens within the host includes a requirement for mitochondrial function for metabolic pathways necessary for virulence (such as the glyoxylate cycle and gluconeogenesis) (2,72), the activation of genes required for mitochondrial respiration during colonization of the central nervous system by C. neoformans (80), and the involvement of mitochondria in sur-vival under oxidative stress in C. albicans, C. neoformans, A. fumigatus, and Paracoccidioides brasiliensis (1,54,56,62), as well as the role of mitochondria in fungal morphogenesis (1,46,56,57,87). With respect to morphogenesis, C. albicans mutants lacking the mitochondrial protein Goa1, as well as those with inactivation of the NADH dehydrogenase Ndh51 or subunits of the mitochondrial pyruvate dehydrogenase complex, all display a defect in switching from an ovoid yeast to a filamentous cell morphology, which is a key aspect of virulence (1,46,57,87).…”
Section: Mitochondria and Virulence Of Human Fungal Pathogensmentioning
confidence: 99%
“…Mycelia were harvested, flash frozen in liquid nitrogen, and ground in a Fastprep apparatus (MP Bio) with glass beads and the RLT buffer provided with the RNA extraction kit (RNeasy plant kit [Qiagen]). For quantitative reverse transcription-PCR (RT-qPCR) analysis, 2 g of freshly extracted total RNA was reverse transcribed with oligo(dT) 15 using Superscript II reverse transcriptase (Invitrogen). The RT-qPCR amplification mixture (10 l) was examined with the LightCycler 480 SYBR green I master kit (Roche) on 2 l of a 1/10 dilution of the reverse transcription reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies indicate that the AOX is upregulated in oxidative stress conditions (14,15). It is developmentally regulated in the pathogenic dimorphic fungus Paracoccidioides brasiliensis (15) and plays an important role in the life cycle of the fungal plant pathogen Moniliophthora perniciosa (16). Recently, it has been shown that the AOX is relevant to the virulence of several human-pathogenic fungi, such as Cryptococcus neoformans (17), Aspergillus fumigatus (18), and Paracoccidioides brasiliensis (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation